Prior Surgery Determines Islet Yield and Insulin Requirement in Patients With Chronic Pancreatitis - Hongjun Wang; Krupa Desai; Huansheng Dong; Stefanie Owzarski; Joseph Romagnuolo; Katherine A. Morgan; David B. Adams (2013)
In Brief Background Total pancreatectomy with islet autotransplantation (TP-IAT) is safe and effective in the management of intractable pain associated with chronic pancreatitis (CP). Prevention of pancreatogenic diabetes after TP-IAT is related to islet yield from the diseased pancreas. The purpose of this study is to compare islet yield and insulin requirement in the 76 patients who underwent different surgical procedures before TP-IAT at the Medical University of South Carolina between 2009 and 2011. Methods Patients were grouped into four categories based on the operation they had before TP-IAT: transduodenal sphincteroplasty/no prior surgery (n=50), Whipple or Beger procedure (n=14), distal pancreatectomy (n=8), or lateral pancreaticojejunostomy (n=4). Islets were harvested from pancreases of those patients at our current good manufacturing practice facility. Total unpurified islets were transplanted into patients via portal vein infusion. Pancreatic fibrosis, islet yield, cell viability, and insulin requirement were measured. Results The pancreases of transduodenal sphincteroplasty/no prior surgery and Whipple or Beger procedure patients were less fibrotic and had higher islet yield compared with those who had distal pancreatectomy or lateral pancreaticojejunostomy. Higher islet yield also correlated with a greater diabetes-free rate and a lesser insulin requirement at the following intervals: preoperative, postoperative, and 6 months after TP-IAT. Conclusions Prior surgery is strongly correlated with the extent of pancreatic fibrosis, islet yield, and insulin requirements in CP patients undergoing TP-IAT. The history of prior pancreatic resection and drainage procedures may be used to predict postoperative islet function and help to determine the optimal timing for TP-IAT in CP patients. Supplemental digital content is available in the article.